2008
DOI: 10.3171/ped/2008/2/9/163
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging for quantitative flow measurement in infants with hydrocephalus: a prospective study

Abstract: Object Raised intracranial pressure (ICP) that is associated with hydrocephalus may lead to alterations in cerebral hemodynamics and ischemic changes in the brain. In infants with hydrocephalus, defining the right moment for surgical intervention based on clinical signs alone can sometimes be a difficult task. Clinical signs of raised ICP are known to be unreliable and sometimes even misleading. Furthermore, when sutures are closed, ICP does not always correlate with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
16
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 68 publications
2
16
0
1
Order By: Relevance
“…The method used in the present study is identical to the one suggested by Leliefeld et al 20 In 2 of the hydrocephalus cases, the CBF was very low initially (27 and 23 ml/100 g/min, similar to Leliefeld and colleagues' findings). However, in 1 case, CBF was normal at 67 ml/100 g/min.…”
supporting
confidence: 69%
See 1 more Smart Citation
“…The method used in the present study is identical to the one suggested by Leliefeld et al 20 In 2 of the hydrocephalus cases, the CBF was very low initially (27 and 23 ml/100 g/min, similar to Leliefeld and colleagues' findings). However, in 1 case, CBF was normal at 67 ml/100 g/min.…”
supporting
confidence: 69%
“…27 Leliefeld et al used an MRI-based technique to simultaneously measure cerebral inflow via the carotid and basilar arteries and brain parenchymal volume to obtain quantitative data on CBF. 20 In a study of 15 infants from 1 day to 7 months of age, the mean CBF before shunting was 25 ml/100 g/min, which increased to 50 ml/100 g/min following treatment with a shunt. A doubling of CBF after shunting suggests a significant increase in vascular resistance before shunt placement as well as rapid improvement with a reduction in resistance post-shunt insertion.…”
Section: ©Aans 2014mentioning
confidence: 99%
“…22 Recently, 2D phase-contrast MRA has shown that carotid and basilar arterial flow rates are reduced in infants with hydrocephalus. 23 However, 2D phase-contrast MRA does not directly measure CBF at the tissue level and may be hampered by long scanning times and flow-sensitive technical challenges. 24,25 In contrast, arterial spin-labeled (ASL) MR imaging perfusion directly measures tissue perfusion without requiring long scanning times, contrast, or radioisotope injection.…”
mentioning
confidence: 99%
“…Nowadays, magnetic resonance is already being used associated with other resources to aim of investigating pathophysiological characteristics of several diseases, mainly the neurological ones [11][12][13] . However, most studies, both experimental and clinical, use MRI equipment of field higher than 1.0T.…”
Section: 1t Magnetic Resonance Image In the Study Of Experimental Hmentioning
confidence: 99%